Implementasi Pertanian Sehat dan Berkelanjutan melalui Pemberdayaan Masyarakat di Desa Mulyoagung, Malang: Implementation of Healthy and Sustainable Agriculture through Community Empowerment in Mulyoagung Village, Malang - Ardiarini, Noer Rahmi; Suyadi, Suyadi (Fakultas Pertanian Universitas Brawijaya, 2025)
Healthy and sustainable agricultural practices emphasize ecosystem balance by rejecting the use of harmful chemicals and adopting organic fertilizers derived from natural sources. In Indonesia, organic agriculture has begun to develop in response to growing public awareness of environmental issues. However, the implementation of these practices continues to face challenges, including limited farmer understanding and participation. The looming threat of climate change further underscores the urgency of adopting sustainable agricultural practices to ensure global food security. A community engagement program on sustainable agriculture was conducted in Tawangargo Village, Malang Regency, aiming to support food self-sufficiency and enhance regional food resilience. The program emphasized collaboration among the government, farmers, and local communities to promote the adoption of sustainable farming practices. This community service activity was carried out from June to September 2024. The primary targets were conventional farmers and residents who had never engaged in cultivation. Additionally, the program involved key stakeholders such as government representatives, academics, and the general public interested in agricultural development in the area. The overarching goal was to deliver broad benefits to the community and improve overall well-being. The implemented activities included: (1) raising awareness of sustainable agriculture through the cultivation of healthy vegetables using liquid organic fertilizer (POC) derived from household materials, (2) distributing Compost Bags to members of the Family Welfare Movement (PKK) to process organic household and yard waste, and (3) providing guidance on the use of Compost Bags and implementing home-based agriculture by utilizing household waste. The results of this community engagement activity indicate that education and assistance in the use of liquid organic fertilizers and Compost Bags effectively increased public awareness regarding the importance of sustainable agriculture and household organic waste management. Through the cultivation of healthy vegetables and the use of household waste as compost materials, the community—particularly PKK women—gained a deeper understanding of environmental stewardship and the application of eco-friendly, home-based agricultural concepts.